Gambaran Tingkat Kecemasan Pada Pasien Stroke di Ruang Belibis RSUD. Wangaya Denpasar - Suputra, Dewa Ketut; Muryani, Ni Made Sri; Sukarja, I Made; Krisnayani, Ni Made Wina (Jurnal Kesehatan Medika Udayana, 2018)
ABSTRACT Background: Stroke is a major cause of disability in adults, where four million Americans experience neurological deficits due to stroke, two-thirds of these deficits are moderate to severe. This disease has become a worldwide health problem and is increasingly important, with two-thirds of strokes now occurring in developing countries. Stroke sufferers themselves will experience a psychological response, namely anxiety because in addition to being a life threat, patients will feel anxious about their future. The purpose of this study was to determine the description of the level of anxiety in stroke patients in the Belibis Room of Wangaya Hospital Denpasar. Methode: The type of design used is descriptive design. Data collection was carried out by the researchers themselves using a standard questionnaire sheet, the Hamilton Anxiety Rating Scale (HARS), with the number of respondents 30 people who were Stroke patients in the Belibis room of Wangaya Hospital Denpasar. Result: The results of this study indicate that the majority of stroke patients in the Belibis room of Wangaya Hospital Denpasar experienced moderate anxiety, namely as many as 17 (56.7%) respondents, mild anxiety as many as 6 (20%) respondents, severe anxiety as many as 6 (20%) respondents, panic 0%, and only 1 (3.3%) respondents who did not experience anxiety. Conclusion: Individuals who experience anxiety are mostly aged over 50 years, female sex, high school education, and have private jobs. It is expected that families can provide motivation and positive encouragement to patients. ABSTRAK Latar Belakang: Stroke adalah penyebab utama kecacatan pada orang dewasa, dimana empat juta orang Amerika mengalami defisit neurologik akibat stroke, dua pertiga dari defisit ini bersifat sedang sampai parah. Penyakit ini telah menjadi masalah kesehatan yang mendunia dan semakin penting, dengan dua pertiga stroke sekarang terjadi di negara – negara yang sedang berkembang. Penderita stroke sendiri akan mengalami suatu respon psikologis, yaitu kecemasan karena selain menjadi suatu ancaman hidup, pasien akan merasa cemas akan masa depannya. Tujuan penelitian ini untuk mengetahui Gambaran Tingkat Kecemasan Pada Pasien Stroke di ruang Belibis RSUD Wangaya Denpasar. Metode: Jenis desain yang digunakan adalah desain deskriptif. Pengumpulan data dilakukan oleh peneliti sendiri dengan menggunakan lembar kuesioner yang sudah baku yaitu Hamilton Anxiety Rating Scale (HARS), dengan jumlah responden 30 orang yang merupakan pasien Stroke di ruang Belibis RSUD Wangaya Denpasar. Hasil: Hasil penelitian ini menunjukkan bahwa sebagian besar penderita stroke di ruang Belibis RSUD Wangaya Denpasar mengalami kecemasan sedang, yaitu sebanyak 17 responden (56,7%), kecemasan ringan sebanyak 6 orang (20%), kecemasan berat sebanyak 6 orang (20%), panik 0%, dan hanya 1 orang (3,3%) responden yang tidak mengalami kecemasan. Simpulan: Individu yang mengalami kecemasan sedang sebagian besar berusia diatas 50 tahun, jenis kelamin perempuan, pendidikan SMA, dan memiliki pekerjaan swasta. Diharapkan keluarga mampu memberikan motivasi dan dorongan positif pada pasien.